ANALISIS PENGARUH KESETARAAN GENDER TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA BARAT - Desi Mariati Padang (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze the effect of 1) gender equality in the field of education 2) gender equality in the health sector 3) gender equality in the field of per capita expenditure. This study uses Indonesian Susenas Statistics data from 2012-2017. The analysis technique used is OLS by using the fixed effect model. The estimation results show that 1) gender equality in education has a positive and significant effect on economic growth in West Sumatra 2) gender equality in the health sector has a negative and significant effect on economic growth in West Sumatra 3) gender equality in the per capita expenditure area has a negative effect and significant to economic growth in West Sumatra. Meanwhile simultaneously the variables of education, health and per capita expenditure have a significant effect on economic growth in West Sumatra.